Cultural diversity scenarios in the urban public space The case of Mouraria neighbourhood (Lisbon) - Menezes, A. P. (2012)
The issues discussed here point to the importance that 'culture' has taken in the contemporary processes of urban intervention, particularly with regard to programs and projects initiated by the prefix 're' – requalification, rehabilitate, revitalize, regenerate. Another set of questions in this discussion refers to the role that urban public space has taken in implementing the urban and cultural interventions. The discussion must be initiated by reference to social dynamics and urban intervention as currently takes place in the neighbourhood of Mouraria, a representative quarter of popular Lisbon. Mouraria experiences an urban condition crossed by numerous setbacks and heterogeneities: an aging population along with the renewal brought by immigrants, precarious living conditions, formal / informal business, traffic and drugs consumption, prostitution. It is also a neighbourhood representative of 'culture' and 'diversity'.